Biogasproduktion in Deutschland: Sollte die energetische Nutzung von Wirtschaftsdünger explizit gefördert werden?; Biogas Production in Germany - Should the Energetic Use of Manure be Explicitly Promoted? - Jochen Thiering; Enno Bahrs (German Journal of Agricultural Economics (GJAE), 2011)
– For the politically desired increase in the use of renewable energies, in particular an increase of biogas production based on agricultural residues such as manure is regarded as beneficial. Although this residue can be supplied without any production costs, the biogas production made in Germany increased especially based on cultivated energy crops. The predominant part of the accruing manure is not used yet. In this paper, therefore, the need for additional promotion of energetic use of manure is discussed. The results based on literature values and investment calculations show that the avoidance of greenhouse gases (GHG) with biogas from manure causes a high potential and low external cost compared to biogas of corn silage. Manure transports influence the costs of GHG mitigation strongly; nevertheless low transport distances may be accepted. However, individual economic barriers exist for the use of manure instead of energy crops. An increase of manure proportion often increases the electricity production costs especially if manure has to be transported. In conclusion, it seems to be appropriate to promote the energy use of manure with the aim of a high utilization of the existing potential and an avoidance of unwanted effects to the land markets.
Keywords: 330